2018
DOI: 10.1044/2018_jslhr-s-17-0393
|View full text |Cite
|
Sign up to set email alerts
|

Bilingual Speech Sound Development During the Preschool Years: The Role of Language Proficiency and Cross-Linguistic Relatedness

Abstract: Purpose The purpose of this study was to investigate typical Spanish–English speech sound development longitudinally in a group of bilingual preschoolers enrolled in a Head Start Program and to examine the extent to which such development is linked to language proficiency. The study also aimed to identify whether speech development is related cross-linguistically and to improve our understanding of error patterns in this population. Method Thirty-five b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 50 publications
8
33
0
Order By: Relevance
“…However, the main finding was that vocabulary was a strong predictor of phonological accuracy across all ages. This ties in with diverse observations in the literature indicating that monolingualbilingual differences in phonology are equally present in younger and older age-groups (Gildersleeve-Neumann et al, 2008: Gildersleeve-Neumann & Wright, 2010, and that MLU (which may exert a similar influence as expressive vocabulary) is correlated with phonology to an equal degree in younger and older groups (Montanari et al, 2018). We do not know until what age vocabulary influences phonology; however, as Figure 3 shows, our data attest to vocabulary effects on some phonological measures (e.g., PVCs) through to six years.…”
Section: Differences Across Age-groupsupporting
confidence: 79%
See 1 more Smart Citation
“…However, the main finding was that vocabulary was a strong predictor of phonological accuracy across all ages. This ties in with diverse observations in the literature indicating that monolingualbilingual differences in phonology are equally present in younger and older age-groups (Gildersleeve-Neumann et al, 2008: Gildersleeve-Neumann & Wright, 2010, and that MLU (which may exert a similar influence as expressive vocabulary) is correlated with phonology to an equal degree in younger and older groups (Montanari et al, 2018). We do not know until what age vocabulary influences phonology; however, as Figure 3 shows, our data attest to vocabulary effects on some phonological measures (e.g., PVCs) through to six years.…”
Section: Differences Across Age-groupsupporting
confidence: 79%
“…We cannot be sure, however, whether the monolingual-bilingual differences reported in these studies reflect language typology, language exposure, or lexical influences. Montanari, Mayr, and Subrahmanyam (2018) predict that cross-linguistic interaction (referred to as 'negative transfer' in their study) should be particularly evident at the early stages of bilingual development when one language is dominant over the other. It should decrease as exposure to and practice with the non-dominant language increases.…”
Section: Bilingual Statusmentioning
confidence: 94%
“…In order to investigate whether the role of maternal education changes after a year of schooling and acculturation, we measure phonological, lexical and morpho-syntactic abilities a) at preschool entry, when children were about 3;6 and dominant in Spanish, and b) after a year of exposure to the language and culture of the school, when children were about 4;6. Previous research with this sample has shown that children's language proficiency and preference change dramatically after just one year of schooling in English (Montanari et al, 2018;Montanari et al, 2019). Therefore, this study also contributes to the discussion as to whether English exposure and instruction in the preschool setting might mitigate any early relation between maternal education and linguistic performance in English or both languages.…”
Section: The Present Studymentioning
confidence: 56%
“…In the present study, we examine Spanish and English phonological accuracy, lexical diversity and utterance length longitudinally in a sample of low-SES bilingual preschoolers with mothers who had either completed primary or secondary education in Spanish in their country of origin, Mexico. We focus on phonological accuracy -children's ability to produce speech soundsbecause while speech sound production has been found to be related to general measures of language proficiency in Spanish-English bilingual preschoolers (Montanari, Mayr & Subrahmanyam, 2018) and to be affected by maternal education in monolingual children (Campbell et al, 2003;Eadie et al, 2015), no study to date has assessed the link between mother's school attainment and bilingual children's accuracy in producing speech sounds. We also focus on lexical variety and utterance length because, although both measures have been shown to be related to maternal education in the monolingual literature (Dollaghan et al, 1999), studies with bilingual children have not examined linguistic performance in terms of these spontaneous production measures.…”
Section: The Present Studymentioning
confidence: 99%
“…Variations in language-specific realizations of specific phonemes, such as voice onset time (VOT) for stop consonants, are established by two years and three months (2;3) old (Deuchar & Clark, 1996). It appears that 3-year-olds acquire complete phonemic inventories for both of their languages at the same rate that monolinguals acquire the inventory of one, with a relatively low level of interference between the two inventories (Fabiano-Smith & Barlow, 2010;Montanari et al, 2018).…”
Section: Newborns Can Already Distinguish Between Languages Of Differmentioning
confidence: 99%